Income and Wealth Distributionin Germany: A Macro-Economic Perspective - Jan Behringer; Thomas Theobald; Till van Treeck (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2014)
Household surveys like the German Socio-Economic Panel (SOEP) notoriously underestimate the degree of income and wealth inequality at the upper end of the distribution. A new approach developed by Thomas Piketty and co-authors therefore analyses tax return data in an attempt at better measuring top incomes and wealth. In the case of Germany, however, this approach faces a number of difficulties. Since 2009, capital incomes are subject to a flat rate withholding tax, levied at source. Moreover, Germany abandoned the wealth tax in 1997. This makes it difficult to measure the distribution of wealth and capital incomes. Moreover, at the conceptual level, top household income shares underestimate the rise of inequality in Germany because much of the shift in income distribution since the early 2000s has taken the form of rising corporate profits, which in large part have been retained by firms and hence are not counted as household income. Despite these problems, measures of income and wealth inequality can be developed by combining information from household surveys and national accounts data. The article also argues that reducing inequality would contribute to reducing Germany's export surplus and thereby enhance macroeconomic stability. – – Freiwillige Haushaltbefragungen wie das Sozioökonomische Panel (SOEP) unterschätzen tendenziell die Ungleichheit von Einkommen und Vermögen. Die von Thomas Piketty und anderen etablierte Forschungsrichtung wertet daher zur Bestimmung der Ungleichheit am oberen Ende der Verteilung amtliche Steuerstatistiken aus. Da in Deutschland seit 2009 Kapitaleinkommensteuern nicht mehr personenbezogen erfasst werden und es überdies keine Vermögenssteuer gibt, gestaltet sich die Erfassung hoher Einkommen und Vermögen jedoch als schwierig. Darüber hinaus führt die Piketty-Methode auch deswegen zu einer Unterschätzung des Anstiegs der Ungleichheit in Deutschland seit der Jahrtausendwende, weil ein großer Teil der steigenden Gewinne von den Unternehmen einbehalten und damit nicht als Haushaltseinkommen erfasst wurde. Trotz dieser Probleme können aussagekräftige Kennziffern der Ungleichheit in Deutschland unter Zuhilfenahme vorhandener Umfragedaten sowie Gesamtwirtschaftlicher Rechenwerke entwickelt werden. Im Report wird zudem argumentiert, dass eine Reduzierung der Ungleichheit in Deutschland könnte zum Abbau der hohen Exportüberschüsse und damit zu mehr makroökonomischer Stabilität beitragen würde.
urn:nbn:de:101:1-201411242568
Keywords: 330